Functional dissection of SPOP at the amino acid level reveals a comprehensive functional landscape of variants during tumorigenesis - Seong Kyun Park; Jeongha Lee; Seon Ju Park; Ye Na Kim; Gi Hyun Shin; Kisoon Dan; Hee-Jung Choi; Dohyun Han; Byung Joon Hwang; Murim Choi (Proceedings of the National Academy of Sciences, 2026)
Numerous proteins display pleiotropic functions in different clinical contexts. However, the molecular mechanism underlying such effects is rarely understood. Speckle-type POZ protein ( SPOP ) is a typical example, exhibiting tumor-suppressing or tumor-promoting effects in different tumor types in accordance with different amino acid changes; specifically, two distinct sets of variants in SPOP are commonly found in subsets of prostate cancer and endometrial cancer patients. To comprehensively characterize the functional landscape of SPOP alteration, we performed a deep mutational screening (DMS), elucidating the functionality of 7,933 out of 8,228 possible single amino acid changes (96.4% coverage). Leveraging the observation that overexpression of human SPOP leads to yeast growth arrest, we assessed the functionality of each variant using a yeast proliferation assay. In addition, our approach combined long-read and short-read sequencing. Finally, our DMS model enables a clear distinction of likely-loss-of-function variants that are enriched in prostate cancers and reveals their differential characteristics in both protein structure and genetic assessments. These results demonstrate the utility of our approach in high-resolution mapping and amino acid–level interpretation of protein function.